Berberine at sub-inhibitory concentration inhibits biofilm dispersal in Staphylococcus aureus. Issue 9 (30th September 2022) - Zhang, Changfeng; Li, Zhongliang; Pan, Qing; Fan, Liping; Pan, Ting; Zhu, Feng; Pan, Qian; Shan, Li; Zhao, Liping
Abstract : Staphylococcus aureus is a major human pathogen, which has multiple drug resistance and can cause serious infections. Recent studies have shown that berberine has antibacterial activity and it can affect biofilm formation of S. aureus . However, the berberine effect on the biofilm of S. aureus is controversial. In this study, we investigate the effect of berberine on the biofilm development in S. aureus NCTC8325 and explore the possible mechanism. Susceptibility test shows that berberine inhibits growth of methicillin-sensitive S. aureus (MSSA), methicillin-resistant S. aureus (MRSA) and vancomycin-intermediate S. aureus (VISA) at different concentrations. S. aureus NCTC8325 is chosen as a model strain to explore further the berberine effect. The MIC of berberine for S. aureus NCTC8325 is 256 µg ml −1 . Berberine below 32 µg ml −1 inhibits the dispersal of biofilm and stimulates clumping of cells of NCTC8325 in a concentration-dependent manner, while not showing obvious inhibition on the bacterial growth. The transcription of the key negative regulator of biofilm dispersal AgrA is decreased and an agrA mutant forms biofilm reaching to a similar level of biomass to WT in the presence of berberine at 32 µg ml −1 . Transcription of some genes involving synthesis of biofilm structure components, including polysaccharide intracellular adhesin (PIA), proteins and eDNA were also up-regulated, especially icaA for PIA synthesis. And consistently, PIA content was increased in cells exposed to berberine at 32 µg ml −1 . This study reveals the dependence of berberine inhibition of biofilm dispersal on the Agr system, which is the first report exploring the molecule mechanism of the berberine effect on the biofilm of S. aureus .